Preparation and Properties of PTFE-PMMA Core-Shell Nanoparticles and Nanocomposites. (10th September 2012) - Antonioli, Diego; Laus, Michele; Zuccheri, Giampaolo; Kapeliouchko, Valerj; Righetti, Maria Cristina; Boarino, Luca; Sparnacci, Katia
Abstract : The preparation of polytetrafluoroethylene-poly(methyl methacrylate) (PTFE-PMMA) core-shell particles was described, featuring controlled size and narrow size distribution over a wide compositional range, through a seeded emulsion polymerization starting from a PTFE seed of 26 nanometers. Over the entire MMA/PTFE range, the particle size increases as the MMA/PTFE ratio increases. A very precise control over the particle size can be exerted by properly adjusting the ratio between the monomer and the PTFE seed. Particles in the 80–240 nm range can be prepared with uniformity indexes suited to build 2D and 3D colloidal crystals. These core-shell particles were employed to prepare nanocomposites with different compositions, through an annealing procedure at a temperature higher than the glass transition temperature of the shell forming polymer. A perfect dispersion of the PTFE particles within the PMMA matrix was obtained and optically transparent nanocomposites were prepared containing a very high PTFE amount.